2021
DOI: 10.1186/s12913-021-07235-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and performance of haemovigilance systems in 10 sub-saharan African countries is sub-optimal

Abstract: Background Haemovigilance is an important element of blood regulation. It includes collecting and evaluating the information on adverse events resulting from the use of blood and blood components with the aim to improve donor and patient safety. We describe the results of the pilot of the integrated GBT+ Blood for the haemovigilance function in 10 sub-Saharan African countries. Methods We piloted the integrated WHO Global Benchmarking Tool plus Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…Haemovigilance programmes play a major role in quality improvement in BTS. In a recent study of 10 sub-Saharan African countries, it was found that a lack of a comprehensive legal framework, a lack of clear understanding, distinction of the function of the blood service and a lack of human resources were major constraints to the implementation and performance of haemovigilance systems [27].…”
Section: Discussionmentioning
confidence: 99%
“…Haemovigilance programmes play a major role in quality improvement in BTS. In a recent study of 10 sub-Saharan African countries, it was found that a lack of a comprehensive legal framework, a lack of clear understanding, distinction of the function of the blood service and a lack of human resources were major constraints to the implementation and performance of haemovigilance systems [27].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the true objective of a Hv is to increase blood transfusion efficiency. As these are widely accredited across all the analytical procedures that assured the quality of blood and its components regarding the improvement of health to save the patient's life during acute emergencies [14][15][16]. Figure 1 is showing the organogram of Hv.…”
Section: Introductionmentioning
confidence: 99%
“…However, their capacity to regulate IVDs was limited. A benchmarking exercise conducted by the PEI BloodTrain in 2018 5 revealed that only three out of ten benchmarked NRAs in Africa have established functional structures for the regulation of medical devices and IVDs. In a 2020 survey (unpublished data) involving NRAs in Africa, conducted by the African Medical Devices Forum, only approximately 30% of participating NRAs had implemented basic level controls for the regulation of IVDs as prescribed in the WHO Global Model Regulatory Framework for Medical Devices including IVD medical devices 6…”
Section: Introductionmentioning
confidence: 99%